Stratigraphy and sedimentology of the Niger Delta - Reijers, T.J.A. (Wydawnictwo Naukowe UAM, 2011)
During the Cenozoic, until the Middle Miocene, the Niger Delta grew through pulses of sedimentation over an oceanward-dipping continental basement into the Gulf of Guinea; thereafter progradation took place over a landward-dipping oceanic basement. A 12,000 m thick succession of overall regressive, offlapping sediments resulted that is composed of three diachronous siliciclastic units: the deep-marine pro-delta Akata Group, the shallow-marine delta-front Agbada Group and the continental, delta-top Benin Group. Regionally, sediment dispersal was controlled by marine transgressive/regressive cycles related to eustatic sea-level changes with varying duration. Differential subsidence locally influenced sediment accumulation. Collectively, these controls resulted in eleven chronostratigraphically confined delta-wide megasequences with considerable internal lithological variation. The various sea-level cycles were in or out of phase with each other and with local subsidence, and interfered with each other and thus influenced the depositional processes. At the high inflection points of the long-term eustatic sea-level curve, floodings took place that resulted in delta-wide shale markers. At the low inflection points, erosional channels were formed that are often associated, downdip, with turbidites in low-stand sediments (LSTs). The megasequences contain regional transgressive claystone units (TST) followed by a range of heterogeneous fine-to-coarse progradational or aggradational siliciclastic (para)sequence sets formed during sea-level high-stand (HST). An updated biostratigraphic scheme for the Niger Delta is presented. It also updates a sedimentation model that takes into consideration local and delta-wide effects of sea-level cyclicity and delta tectonics. Megasequences were formed over time intervals of ~5 Ma within individual accurate megastructures that laterally linked into depobelts. The megasequences form the time-stratigraphic frame of the delta and are the backbone for the new delta-wide lithostratigraphy proposed here. Such a new lithostratigraphy is badly needed, in particular because of the vigorous new activity in the offshore part of the Niger Delta (not covered in this contribution). There, as well as in the onshore part of the delta, the traditional lithostratigraphic subdivision of the Cenozoic Niger Delta section into three formations is insufficient for optimum stratigraphic application; moreover, the various informal subdivisions that have been proposed over time are inconsistent.
Keywords: Niger Delta; biostratigraphy; sedimentology; mega sequences; Cycles